Developing the Regression Relationships for the Critical Period of the Reservoir Systems at Sungai Bekok and Sungai Kesang Catchments in Malaysia. Issue 1 (September 2020) - Oskoui, I S; Abdullah, R
Abstract: The knowledge of critical period (CR) for determining the behavior type of reservoir systems is very beneficial in the planning process for distinguishing the period of the required streamflow data in the simulation procedure. Generally, for within-year systems (CR < twelve months) utilizing the critical twelve months of the flow data record is required, whereas for the carryover systems (CR > twelve months) employing the annual streamflow data will suffice. Currently, there is no relationship in the literature that can be used for predicting the behavior type of reservoir systems employing reliability and vulnerability performance indices in Sungai Bekok and Sungai Kesang catchments. Hence, the objective of this study is to develop a novel equation involving performance indices for estimating the critical period of the aforementioned reservoir systems. The reservoirs were analyzed employing a Monte Carlo technique by improved sequent peak algorithm. Afterward, new regression equations for the critical period were developed based on simulation results and then verified by comparing the equations' outcomes with simulation results. Finally, it was found that the performance of the new equations is excellent in reproducing the critical period.